AUTOIMMUNE ENCEPHALITIS: DIAGNOSTIC AND TREATMENT APPROACH - Hamdani, Ismi Adhanisa; Agustina, Lydia; Sasongko, Hari Andang; Gaharu, Maula Nuruddin; Rachmatullah, Fahmi; Ghufira, Nanda; Stevany, Nabila; Pawestri, Natasya Rahma Dewi; Fatahuddin, Rahaliya Salsabila; Natasya, Natasya (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2024)
Autoimmune encephalitis is a type of brain inflammation induced by an inappropriate immune response to a neuronal antigen, resulting in the generation of autoantibodies. Autoimmunity as important cause of encephalitis in recent years has not been much reported in Indonesia. Increased familiarity with autoimmune encephalitis among physician, not only neurologist, is extremely important for early detection. Prompt diagnosis and early immunotherapy leads to better prognosis in this potentially treatable disease, despite a long disease course. Autoimmune encephalitis is characterized by acute-subacute progressive neuropsychiatric symptoms with associated cognitive dysfunction, encephalopathy, psychiatric disorders, movement disorders and seizures, with anti-N-methyl-D-aspartate (NMDA) receptors encephalitis as the most common type. In addition to clinical features, further diagnostic investigations needed are brain magnetic resonance imaging (MRI), electroencephalography (EEG), cerebrospinal fluid (CSF) analysis, and autoantibody testing. Challenges in establishing diagnosis include wide range of clinical symptoms, absence of abnormalities in brain MRI, unspecified EEG findings, negative antibody testing, and limited availability of antibody testing in Indonesia. This literature review discusses the recognition, diagnosis and principle of treatment of autoimmune encephalitis.